The Role of Financial Distress on Company Life Cycle and Stock Return - Akhmad Sigit Adiwibowo; Dwi Safiatun Rohmah; Putri Nurmala (JAK (Jurnal Akuntansi) Kajian Ilmiah Akuntansi, 2023)
This study aims to see how the company life cycle affects stock returns with financial distress as a moderating variable in companies listed on the Indonesia Stock Exchange between 2017 and 2021. Purposive sampling was used to obtain a sample of 71 companies. A panel regression analysis with a fixed effect model was used for the analysis. The study's findings show that the decline stage of a company's life cycle hurts stock returns, whereas the introduction, growth, and maturity stages do not affect stock returns. Financial distress can mitigate the impact of the company's decline stage on stock returns. However, it needs to mitigate the impact of the company's introduction, growth, and maturity stages on stock returns.